Fashion, Identity, Image - Jobling, Paul; Nesbitt, Philippa; Wong, Angelene (Bloomsbury Visual Arts, 2022)
How has the fashion industry responded to turn-of-the-millennium non-binary identities? Do they have a supportive or exploitative relationship with queer, trans and ageing subjects? Fashion, Identity, Image unpacks these questions and many more in relation to clothing and representation, identity and body politics in British, European and American culture between 1990 and 2020. Jobling, Nesbitt and Wong explore issues of intersectionality and inclusivity through groundbreaking shows, including Maria Grazia Chiuris We Should All Be Feminists catwalk show for Dior (Spring-Summer 2017), Alexander McQueens The Widows of Culloden collection (Fall-Winter 2006), and the role of transgender models such as Oslo Grace since 2015. Looking to the future of our relationship with fashion, theres also an investigation of the android as a redemptive figure in Alessandro Micheles cross-cultural cyborg collection for Gucci (Autumn-Winter 2018/2019) and the impact of the ageing population with analysis of age and memory in work such as Magali Nougarèdes Crossing the Line (2002), and pleasure and morality in fashion publicity since the 1990s for the likes of Calvin Klein, DandG and American Apparel